Faktor Penentu Perilaku Berwirausaha Dikalangan Wanita Muslim: Bukti Empiris di Kota Banda Aceh - Maisi Tania Putri; Khairul Amri; Seri Murni (Jurnal Ekonomi Manajemen dan Sekretari, 2023)
This research uses quantitative methods by obtaining sources from primary and secondary data. The aim is to determine the effect of environmental factors, capital and Islamic religiosity on entrepreneurial behavior among Muslim women in the new Atjeh market, Banda Aceh city. The population in this study were traders in the new Atjeh market on the 3rd floor with a sample of 55 respondents using the slovin formula. The data analysis technique in this study used multiple linear regression using SPSS statistics 22. The results of this study indicate that partially family environment factors and capital factors have a significant positive effect on entrepreneurial behavior among Muslim women in the New Aceh market. Meanwhile, Islamic religiosity has a positive and insignificant effect on entrepreneurship among Muslim women in the New Aceh market. Simultaneously family environment, capital and religiosity have a significant effect on entrepreneurial behavior among Muslim women.